The prognostic values of lymph node ratio for gynecological cancer: a systematic review and meta-analysis - Chen, Mengmeng; Wang, Yisi; Chen, Yali; Han, Ling; Zheng, Ai (Frontiers in Oncology, 2024)
BackgroundThe aim of this study was to determine the relationship between the lymph node ratio (LNR) and the prognostic values of gynecological cancer.Materials and methodsPubMed, Web of Science, Embase, and the Central Cochrane Library were used to search for studies on LNR and gynecological cancer published before 18 April 2024. The effect measure for meta-analysis of primary outcomes was the hazard ratio (HR) for overall survival (OS), progression-free survival (PFS), and disease-free survival (DFS). Pooled HRs and 95% confidence intervals (CIs) were calculated using random- or fixed-effects models. Sensitivity analysis was applied to evaluate the robustness of the results. The I2 statistic was used to measure heterogeneity. Subgroup analysis and meta-regression were chosen to illustrate the potential heterogeneity of the risk factors for outcomes. Publication bias was assessed using Egger’s test and Begg’s funnel plots.ResultsA total of 34 studies with 23,202 cases were included in this meta-analysis. A meta-analysis found that higher LNR was associated with worse OS (HR = 2.42, 95% CI: 2.07–2.83; I2 = 77.4%, p < 0.05), PFS (HR = 1.97, 95% CI: 1.66-2.32; I2 = 0.00%, p > 0.05), and DFS (HR = 3.18, 95% CI: 2.12–4.76; I2 = 64.3%, p < 0.05). Moreover, meta-analysis revealed significant differences in the association between LNR and OS of cervical cancer (CC) (HR = 2.53, 95% CI: 1.94–3.31; I2 = 72.6%, p < 0.05), ovarian cancer (OC) (HR = 2.05, 95% CI: 1.66–2.54; I2 = 76.7%, p < 0.05), endometrial cancer (EC) (HR = 2.16, 95% CI: 1.48–3.16; I2 = 53.6%, p < 0.05), and vulvar cancer (VC) (HR = 8.13, 95% CI: 3.41–19.43; I2 = 57.2%, p < 0.05).ConclusionWe observed a clear association between higher LNR and poorer prognosis in our study of patients with gynecological cancer. Further prospective studies are warranted to determine the optimal LNR and whether LNR can guide adjuvant therapy use in gynecological cancer. It is essential to conduct further prospective studies to establish the optimal LNR threshold, determine the minimum threshold of lymph node removal, and investigate whether LNR can serve as a reliable marker for guiding adjuvant therapy choices in gynecological cancer.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/#recordDetails, CRD42024541187.